Implementation of the Teacch Approach on Repetitive Behavior and Limited Interest in Children with Autism - Kenila, Elisabet (Department of Special Education, 2022)
One of the main disorders in children with autism is repetitive behavior and limited interest. The purpose of this study was to describe 1) planning, 2) implementation and 3) evaluation of the implementation of the TEACCH approach on behavior and limited interests in children with autism. The research method uses a qualitative research design with a case study approach. Data were obtained through observation and documentation, open questionnaires and discussions with therapists and caregivers at the Autism Therapy Unit of Bhkati Luhur in Malang. Results: 1) Planning: there is training to find out the TEACCH approach, recurrent disorders in children with autism, the impact and handling of strategies, 2) the implementations are; Structuring the environment, assessment, making visual programs and schedules, regular and structured and collaborative intervention 3) Evaluation: Children with autism are more organized, more independent, increased in receptive communication, more focused, control emotions, and are confident. Some children with severe disabilities are still need some assistance.